Concentration of survivin in children with oligo- and polyarticular juvenile idiopathic arthritis (JIA): diagnostic and prognostic value—a single-center study - Joanna Lipinska (Arthritis Research & Therapy, 2021)
Abstract Aim The goal of the study was to assess the diagnostic and prognostic utility of survivin in patients with juvenile idiopathic arthritis (JIA). Methods Seventy children with JIA—59 newly diagnosed and 11 biologically treated (46 girls and 17 boys) aged 1.5–18 years and 29 healthy children as a control group, appropriately matched in terms of sex and age, were included in the study. The disease activity was established on the basis of the JADAS-27 criteria. The concentration of survivin was assessed by an ELISA test in serum and also 18 matched synovial fluid samples collected from patients with JIA. Results Children with JIA were divided according to the subtype of the JIA. In 65.7% of patients, oligoarthritis was diagnosed. The largest group comprised children of low disease activity (62.9%) according to JADAS-27. The serum concentration of survivin was significantly higher in children with JIA compared to the controls (p < 0.001). The concentration of survivin was higher among patients positive for anti-cyclic citrullinated peptide autoantibodies (ACPA) (p = 0.001). In all synovial fluid samples, the concentration of survivin was higher than in matched serum (p = 0.003). Serum survivin concentration was not significantly associated with radiological damage status or active synovitis assessed by joint ultrasonography. Survivin level was not significantly associated with disease duration time or treatment with TNF-α inhibitors in DMARD’s non-responders. Conclusions Survivin should be considered as a biomarker of joint inflammation helpful in the diagnosis of oligo- and polyarticular JIA and probably not dependent on treatment with TNF-α inhibitors.